The Evolution of Climate Changes in Portugal: Determination of Trend Series and Its Impact on Forest Development - Nunes, Leonel (2020)
Climate changes are a phenomenon that can a ect the daily activities of rural communities, with particular emphasis on those directly dependent on the agricultural and forestry sectors. In this way, the present work intends to analyse the impact that climate changes have on forest risk assessment, namely on how the occurrence of rural fires are a ecting the management of the forest areas and how the occurrence of these fires has evolved in the near past. Thus, a comparative analysis of the data provided by IPMA (Portuguese Institute of the Sea and the Atmosphere), was carried out for the period from 2001 to 2017 with the climatic normal for the period between 1971 to 2000, for the variables of the average air temperature, and for the precipitation. In this comparative study, the average monthly values were considered and the months in which anomalies occurred were determined. Anomalies were considered in the months in which the average air temperature varied by 1 C than the value corresponding to the climatic norm, in at least 50% of the national territory. The same procedure was repeated for the variable precipitation, counting as anomaly the occurrence of a variation in precipitation of 50%, also in 50% of the national territory. Then the calculation of the moving averages for cycles of 3, 5 and 7 periods were applied, and the trend lines were projected. Subsequently, the relationship between the results obtained and the occurrence of rural fires as well as the spatial distribution of forest area, species and structure were analyzed. From the results obtained it was possible to confirm the existence of a tendency for the occurrence of climatic anomalies, highlighting the occurrence of an increasing number of months with temperatures higher by at least 1 C. It was possible to foresee the relation between the occurrence of rural fires and the periods of anomaly and absence of precipitation. From the results obtained it is also possible to infer that, analyzing the tendency for these phenomena to occur, it can be necessary to change the “critical period of rural fires”, since it is verified that what is currently in use does not covers the entire period where anomalies occur and where large-scale rural fires potentially can happen.